ANALISIS PENILAIAN KEPUTUSAN INVESTASI MENGGUNAKAN METODE NET PRESENT VALUE - Slamet Heri Winarno (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2014)
Investment for most companies is the development of the activity as a business is run. Investment capital investment not only alone, but also on other matters relating to the use of funds, such as the purchase of assets, asset replacement and others. Management of the investment must be done carefully which of course will produce optimal returns. For measurements that need to be done on assessing the viability of an investment. This paper attempts to provide an overview of the use of methods that are commonly used in assessing an investment. Through a comparison between several methods such as average rate of return, payback period, internal rate of return, profitability index, and Net Present Value (NPV), the results showed that the NPV method can be regarded as a more representative method to generate the feasibility and optimization of the investment.Keywords: Assessment, Investment, Net Present Value